Analysis of gravity data for extracting structural features of the northern region of the Central Indian Ridge - Thanh Pham, Luan; Prasad, K.N.D. (Vietnam Journal of Earth Sciences, 2023)
In this study, structural lineaments and fracture zones of the northern region of the Central Indian Ridge have been determined using gravity data from XGM2019e_2159 global gravity model. In this scope, firstly, the edge detection performances of the gradient amplitude of the tilt angle (THDR), theta map (TM), improved local phase (ILP), and improved logistic (IL) methods have been evaluated on synthetic examples. The results show that the IL method effectively avoids false edges and produces high-resolution edges. Then, the methods are applied to the gravity anomaly of the northern region of the Central Indian Ridge. It has been determined that the most prominent structural lineaments observed over the region are in the NE-SW and NW-SE directions. These trends match reasonably with the significant trends of the Tilt depth solutions that show a depth range of 2.2 km to 7 km for different geological structures. In addition, the obtained results are compatible with the known fracture zones of the study area. The findings help us to improve our understanding of the structure and tectonic framework of the study region.